The effect of simulated altitude training on basketball performance - Smith, H. K. (Lincoln University Digital Thesis, 2020)
The aim of this study was to investigate whether adding hypoxia to 4 weeks of repeated sprint and high-intensity training improved explosive muscular power, aerobic performance and repeated sprint ability in 3x3 basketball players. Nine well trained female basketball players, were randomly assigned to a hypoxia group (H) (n = 4; age: 20.0 ± 1.6; height: 169.4 ± 4.6; body mass: 76.9 ± 6.5; haemoglobin: 135.8 ± 4.1) or control (C) group (n = 5; age: 20.8 ± 2.2; height: 174.7 ± 5.2; body mass: 68.0 ± 4.3; haemoglobin: 128.2 ± 11.3). The training programme applied during the study was the same for both groups, but with different environmental conditions during the selected interval training sessions. All subjects performed two high intensity interval training sessions per week in addition to two team trainings for a total of 4 weeks. During the interval training sessions the trained in a normobaric hypoxic chamber at a simulated altitude of 3000 m (FIO2 = 15.3%), while the Control group performed similar training under normoxia conditions (FIO2 = 21.0%), also inside the chamber. Players were blinded to the oxygen concentration in the chamber. Training sessions consisted of 6 sets of 30s reps with 30s rest between reps and 1 min rest between sets for a total of 60 min per training session. Approximately 1 week before and 1 week after training, explosive muscular power (counter-movement jump peak power, peak velocity and distance) aerobic performance, (Yo-Yo Intermittent Recovery Test L1) and repeated sprint ability (number of times players covered a 17 m distance in 1 min) were measured. Changes in the measurement variables from baseline to post-training along with standard deviations representing the between-and within-subject variability were estimated using a mixed modelling procedure in the Statistical Analysis System (Version 9.3, SAS Institute, Cary, North Carolina, USA). At baseline the two groups were similar in all characteristics apart from repeated sprint ability where the control group was able to cover significantly more ground during the test (8.5 ± 5.6 m, mean ± 95% CI) and height where the control group was significantly taller than hypoxic group (5.3 ± 3.7 cm, p = 0.02). Compared to the control group, the hypoxic group showed an increase in distance covered during the repeated sprint test (9.1 ± 9.0 m, p = 0.05), as a result of training, however, all other variables showed unclear differences between the groups. Adding hypoxia to high intensity training in these athletes appears to improve repeated sprint ability in female 3x3 basketball players, however, the effect of hypoxia on muscular power and aerobic fitness was unclear.